Using technology acceptance model for exploring pre-service teachers’ perception towards online learning - Tan, Choon Keong; Lee, Kean Wah; Stennia Miga Anak Radin (Penerbit Universiti Malaysia Sabah, 2016)
The peiceived attitudes towards e-learning is an important factor for pre-service teachers when engaging e-learning systems at the university. The purpose of this paper is to examine the behaviour of pre-service teachers towards the use of e-learning in a social science subject via Technology Acceptance Model (TAM). Four TAM dimensions namely perceived usefulness (PU), perceived ease of use (EU) and their influences on satisfaction (SN) and intention to use (IN) were explored. A survey was given to 69 pre-service teachers pursuing Bachelor of Education programme in a public university in Sabah, East Malaysia. The results revealed that there were moderate level of acceptance in the observed PU (mean=3.82), EU (mean=3.52), SN (mean=3.35) and IN (mean=3.82). The relationships analysis showed that PU influenced the intention to use online courses strongly (r = .63) and on the other hand EU also had strong influence on SN (r = .68). The study also found that the mean score for PU (3.82) was higher than EU (3.52) which implicated that the design, pedagogical and navigational aspects of a course are important to obtain good SN and IN scores from the users.